The Development of Problem-Based Learning Interactive Teaching Material to Improve Mathematical Communication Skills and Learning Resilience - Hardiana, Analisa; Putra, Harry Dwi ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2026)
Mathematical communication skills and learning resilience are essential competencies for success in mathematics learning in the 21st century. However, Indonesian students still show low achievement in these aspects, as reflected in PISA results and classroom learning practices. This study aimed to develop and examine the effectiveness of Problem-Based Learning (PBL)-based teaching materials assisted by the Canva interactive web platform to improve students’ mathematical communication skills and learning resilience. This research employed a Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The study involved 60 tenth-grade students of MAN 4 Sukabumi, divided into an experimental group and a control group. The experimental group learned using PBL-based teaching materials assisted by Canva, while the control group received conventional instruction. The research instruments included expert validation sheets, student and teacher response questionnaires, a mathematical communication test consisting of four essay items, and a learning resilience scale with 30 statements. Data were analyzed using descriptive statistics and inferential statistical tests. The results showed that the developed teaching materials were categorized as very valid and highly practical. Students in the experimental group achieved higher mathematical communication scores and learning resilience compared to the control group, with moderate N-Gain improvements. Statistical analysis confirmed a significant difference between the two groups (p < 0.05). It can be concluded that PBL-based teaching materials assisted by the Canva interactive web platform are effective in improving students’ mathematical communication skills and learning resilience.